Neurokinin 3 Receptor Antagonists Do Not Increase FSH or Estradiol Secretion in Menopausal Women - Prague, Julia K (J Endocr Soc, 2019)
BACKGROUND: Neurokinin 3 receptor (NK3R) antagonism is a promising novel treatment for menopausal flashes. However, to avoid adverse hormonal effects it is clinically important to first confirm whether gonadotropin and estradiol concentrations change as a result of their administration. METHODS: Single-center, randomized, double-blind, placebo-controlled, crossover trial of an oral NK3R antagonist (MLE4901) in 28 women aged 40 to 62 years, experiencing >7 hot flashes/24 h; some bothersome or severe (Clinicaltrials.gov, NCT02668185). Weekly serum gonadotropins and estradiol levels were measured using commercially available automated immunoassays a priori. Serum estradiol was also measured post hoc using a highly sensitive direct assay by liquid chromatography tandem mass spectrometry. Hormone levels were compared by the paired sample t tests or by the Wilcoxon matched-pairs signed rank test, as appropriate for the distribution of the data. RESULTS: Mean (standard deviation) serum follicle-stimulating hormone (FSH) concentration was not significantly increased when taking MLE4901 (72.07 ± 19.81 IU/L) compared to placebo (70.03 ± 19.56 IU/L), P = .26. Serum estradiol was also not significantly altered, irrespective of which assay method was used (median interquartile range of serum estradiol by immunoassay: placebo 36 ± 3 pmol/L, MLE4901 36 ± 1 pmol/L, P = .21; median serum highly sensitive estradiol: placebo 12 ± 16 pmol/L, MLE4901 13 ± 15 pmol/L, P = .70). However, mean (standard deviation) serum luteinizing hormone concentration significantly decreased with MLE4901 (27.63 ± 9.76 IU/L) compared to placebo (30.26 ± 9.75 IU/L), P = .0024. IMPLICATION: NK3R antagonists do not increase serum estradiol or FSH despite their reduction in hot flashes. This is clinically significant and highly reassuring for women who have a contraindication to conventional hormone therapy such as prior/existing breast cancer and/or thromboembolism.